Comparison of the Cyclic Variation of a Diesel-Ethanol Blend in a Diesel Engine - Mohd Hafizil, Mat Yasin; Ahmad Fitri, Yusop; R., Mamat; Abdul Adam, Abdullah; N. H., Badrulhisham (IOP Science, 2018)
Alcohols are renewable and sustainable second generation biofuels which are derived from various biomass feedstock sources. These fuels with similar properties to mineral diesel can be used as a blend or additive to improve the combustion characteristics and pollutant emissions in the automotive engines. However, different fuel properties characterize different combustion phasing parameters for the specific engine operation and test condition. This paper presents the preliminary results of coefficient of variations of IMEP (COVIMEP) and Pmax (COVPmax) for a diesel engine fuelled with mineral diesel (B0) and DE10 blend at full load both engine speeds of 1100 rpm and 2300 rpm. The influence of ethanol content in a blend of diesel on the cyclic combustion variations is explained in the calculation values of the coefficient of cyclic variation (COV). The experimental results showed the DE10 fuelling exhibited larger cyclic variations than mineral diesel (B0) at the same test conditions, owing to the reduction of combustion temperature during combustion phasing and lower reactivity of ethanol.